2012
DOI: 10.1002/ajp.22033
|View full text |Cite
|
Sign up to set email alerts
|

Agroecosystems and Primate Conservation in The Tropics: A Review

Abstract: Agroecosystems cover more than one quarter of the global land area (ca. 50 million km(2) ) as highly simplified (e.g. pasturelands) or more complex systems (e.g. polycultures and agroforestry systems) with the capacity to support higher biodiversity. Increasingly more information has been published about primates in agroecosystems but a general synthesis of the diversity of agroecosystems that primates use or which primate taxa are able to persist in these anthropogenic components of the landscapes is still la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0
13

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 96 publications
4
123
0
13
Order By: Relevance
“…Our findings that a large number of primate species were main DCAs are consistent with that of Estrada et al [76] who showed that globally agricultural landscapes, such as orchards, crop farms and forestry plantations, were raided by approximately 57 different primate taxa in agro-ecosystems in which PAs and forestry or fruit plantations are contiguous. High levels of forest fragmentation and agricultural infringement were implicated as the cause of human-primate conflict [76]. The ability of primates to adapt to anthropogenic-dominated agricultural ecosystems and their often overlapping diets with humans brings them into conflict with farmers [76,77].…”
Section: Vulnerability Of Conflict Speciessupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings that a large number of primate species were main DCAs are consistent with that of Estrada et al [76] who showed that globally agricultural landscapes, such as orchards, crop farms and forestry plantations, were raided by approximately 57 different primate taxa in agro-ecosystems in which PAs and forestry or fruit plantations are contiguous. High levels of forest fragmentation and agricultural infringement were implicated as the cause of human-primate conflict [76]. The ability of primates to adapt to anthropogenic-dominated agricultural ecosystems and their often overlapping diets with humans brings them into conflict with farmers [76,77].…”
Section: Vulnerability Of Conflict Speciessupporting
confidence: 92%
“…as exceptional examples that cause extensive damage to crops in Uganda and Ethiopia, and they were perceived by subsistence farmers as the greatest threats to crop yields [17,75]. Our findings that a large number of primate species were main DCAs are consistent with that of Estrada et al [76] who showed that globally agricultural landscapes, such as orchards, crop farms and forestry plantations, were raided by approximately 57 different primate taxa in agro-ecosystems in which PAs and forestry or fruit plantations are contiguous. High levels of forest fragmentation and agricultural infringement were implicated as the cause of human-primate conflict [76].…”
Section: Vulnerability Of Conflict Speciessupporting
confidence: 88%
See 1 more Smart Citation
“…Accordingly, fruits of the exotic oil palm were frequently consumed in the young secondary forests (51.8% of feeding on fruits), while seeds of native manilkaras were frequently swallowed in the old secondary forests (31% of feeding on fruits). The mixture of exotic species and native trees could be used favourably in species management for conservation, as the exotic species supplement the capuchins' food needs [Gosper and Vivian-Smith, 2009;Estrada et al, 2012]. However, the high consumption of oil palm seeds may not provide all the required nutrients, and different food items are needed to balance the capuchins' nutrient intake.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence supporting the idea that agroecosystems can (1) provide temporal habitat for migrating taxa (e.g., birds) and/or (2) extend the available habitat and increase resource availability for resident species (Estrada et al, 1999(Estrada et al, , 2012Perfecto and Ambrecht, 2003;Perfecto and Vandermeer, 2008;Rice and Greenberg, 2000). Only recently, studies have begun to assess the ability of primates to survive within agroecosystems (Estrada et al, 2012).…”
Section: Introductionmentioning
confidence: 97%